Effects of spatial and temporal variation in environmental conditions on simulation of wildfire spread. (May 2015) - Hilton, J.E.; Miller, C.; Sullivan, A.L.; Rucinski, C.
Abstract: Environmental conditions, such as fuel load and moisture levels, can influence the behaviour of wildfires. These factors are subject to natural small-scale variation which is usually spatially or temporally averaged for modelling fire propagation. The effect of including this variation in propagation models has not previously been fully examined or quantified. We investigate the effects of incorporating three types of variation on the shape and rate of propagation of a fire perimeter: variation in combustion conditions, wind direction and wind speed. We find that increasing the variation of combustion condition decreases the overall rate of propagation. An analytical model, based on the harmonic mean, is presented to explain this behaviour. Variation in wind direction is found to cause the development of rounded flanks due to cumulative chance of outward fluctuations at the sides of the perimeter. Our findings may be used to develop improved models for fire spread prediction. Graphical abstract: Highlights: Implementation of a wildfire spread model based on the level set method. Investigation of wildfire propagation under stochastic wind and fuel conditions. Local variation in combustion condition slows the rate of propagation. Local variation in wind direction is found to increase flank spread. A harmonic mean is preferential for spatially varying parameters in spread models.